2022
DOI: 10.1021/acsanm.2c01520
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur-Functionalized Titanium Carbide Ti3C2Tx (MXene) Nanosheets Modified Light Absorbers for Ambient Fabrication of Sb2S3 Solar Cells

Abstract: Modifying light-harvesting photoactive materials via doping and/or functionalization approaches is an effective approach for enhancing the efficiency and stability of solar cells. Herein, sulfur-functionalized two-dimensional (2D) transition-metal carbide (S-MXene) nanosheets are synthesized and introduced as doping agents into the Sb2S3 light absorbers for solar cells. Furthermore, Sb2S3 solar cells are fabricated in two different experimental environments including an inert gas (argon) and ambient conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…The device fabricated in air is expected to give high performance with well-grown cuboidal structures due to the presence of O and S as codopants compared to an inert atmosphere (Ar). 109…”
Section: Functionalization Of Mxenementioning
confidence: 99%
“…The device fabricated in air is expected to give high performance with well-grown cuboidal structures due to the presence of O and S as codopants compared to an inert atmosphere (Ar). 109…”
Section: Functionalization Of Mxenementioning
confidence: 99%
“…Metal chalcogenide semiconductors, consisting of CuS, CdSe, CuInS 2 , Bi 2 S 3 , In 2 S 3 , CdS, CdTe, PbS, and Sb 2 Se 3 , have piqued the interest of the PV community in this area since they offer lower production costs as well as many other appealing qualities such as high transparency and flexibility. 3 In semiconducting materials, Shockley−Read−Hall (SRH) recombination can be helped along by traps if the particles have high energy levels and large capture cross sections. SRH recombination decreases the solar cell performance by causing open-circuit voltage (V OC ) loss, which is the biggest problem in the production of high-performance solar cell materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Because of this, scientists and engineers have been working hard to find and make new kinds of solar cells. Metal chalcogenide semiconductors, consisting of CuS, CdSe, CuInS 2 , Bi 2 S 3 , In 2 S 3 , CdS, CdTe, PbS, and Sb 2 Se 3 , have piqued the interest of the PV community in this area since they offer lower production costs as well as many other appealing qualities such as high transparency and flexibility . In semiconducting materials, Shockley–Read–Hall (SRH) recombination can be helped along by traps if the particles have high energy levels and large capture cross sections.…”
Section: Introductionmentioning
confidence: 99%
“…Here, Gunenthiran et al from the University of Adelaide engineered nanoporous anodized alumina for developing photonic crystals . Separately, Myagmarsereejid et al, in a joint work between Griffith University and the University of Queensland, reported that functionalization of titanium carbide MXene nanosheets with sulfur could be used as an efficient light absorber for solar cells . In a joint work between the University of Technology Sydney and RMIT, Yamamura et al investigated the introduction of defects into nitrogen-doped Ga 2 O 3 nanowires to enhance luminescence .…”
mentioning
confidence: 99%
“…9 Separately, Myagmarsereejid et al, in a joint work between Griffith University and the University of Queensland, reported that functionalization of titanium carbide MXene nanosheets with sulfur could be used as an efficient light absorber for solar cells. 10 In a joint work between the University of Technology Sydney and RMIT, Yamamura et al investigated the introduction of defects into nitrogen-doped Ga 2 O 3 nanowires to enhance luminescence. 11 Ultimately, Low et al from RMIT investigated strain modulation of the optoelectronic characteristics of 2D black phosphorus.…”
mentioning
confidence: 99%